Exploring Motivations, Benefits, and Challenges Adopting Inclusive Business Model: Insights from a Case Study of Palm Oil Industry in Johor - Wan Mahdi, Wan Muhammad Idham; Wan Yusoff, Wan Fauziah (International Journal of Sustainable Construction Engineering and Technology, 2023)
Palm oil is acknowledged as one of the commodities contributing to Malaysia's economic development, specifically as a strategy to eradicate poverty in rural areas. Despite the significant development of the industry, several issues, especially involving palm oil smallholders, require further development. Therefore, this study uses a qualitative research approach to explore adopting a multinational company's inclusive business model (IBM) as a strategy to enhance the industry and the well-being of society specifically palm oil smallholders in Johor. Based on secondary data and interviews, this study discovered that the company is motivated to adopt IBM in the project to ensure the sustainability of raw materials and as one of the company's corporate social responsibility (CSR) activities. The adoption of IBM will also benefit the company, the palm oil smallholders, and the palm oil industry, especially in Johor. Nevertheless, to ensure the sustainability of IBM, a few challenges need to be addressed particularly the complexity of the industry that involves many key players. In conclusion, IBM is able to create value for all stakeholders involve by integrating them in the whole value chain of palm oil industry.